Endoscopic papillectomy for ampullary adenomas in familial adenomatous polyposis - Wehling, Cyrill; Eckstein, Yoana; Stenzinger, Albrecht; Ganion, Nicole; Bruckner, Thomas; Sauer, Peter; Zhang-Hagenlocher, Christine; Kantowski, Marcus; Koschny, Ronald (Familial cancer, 2025)
Objectives of the study were to determine the success, complication and recurrence rate of endoscopic papillectomies in familial adenomatous polyposis (FAP) patients. Ampullary adenoma is frequent in familial adenomatous polyposis (FAP) patients. Endoscopic papillectomy is technically demanding for laterally spreading ampullary adenomas and bleeding, perforation and pancreatitis represent typical complications. 40 FAP patients undergoing endoscopic papillectomy were retrospectively analyzed. Data on periprocedural complications, histopathology, resection techniques and success were collected. Endoscopic papillectomy was performed in 21 male and 19 female patients. Mean adenoma size was 14 mm (8-40 mm). Additional mucosal resection was performed in 45%. Immediate and delayed bleeding occurred in 33% (n = 13) and 13% (n = 5), respectively. Bleeding was associated with male sex and pancreatic endoprosthesis. Endoscopically manageable perforation occurred in 2 patients. Acute pancreatitis occurred in 25% (n = 10) and was significantly associated with female sex. Histopathology revealed papillitis in 5% (n = 2), adenoma with low-grade dysplasia in 73% (n = 29), high-grade dysplasia in 13% (n = 5), and adenocarcinoma in 5% (n = 2). Cumulative recurrence-free resection was achieved in 94% (n = 33/35) after a mean of 1.4 procedures at a median follow-up of 591 days (range 15-2605). Endoscopic papillectomy shows a high clinical success in FAP patients even with laterally spreading adenoma. Adenoma recurrence can be successfully treated with a limited number of reinterventions.
Online veröffentlicht: 4. November 2025
Gesehen am 03.02.2026